Analisis Faktor-Faktor Yang Mempengaruhi Kualitas Laba pada Perusahaan Subsektor Gas dan Minyak Bumi yang Terdaftar di Bursa Efek Indonesia - Fatimah, Siti; Rimawan, Rimawan; Huda, Nurul (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2024)
This study aims to analyze the factors that affect the quality of profits. The method used is quantitative, with a data collection method through secondary data, namely the financial statements of 3 gas and petroleum subsector companies listed on the IDX for 2018-2022. The data analysis techniques used were classical assumption test, multiple linear regression analysis, determination coefficient test, and hypothesis test. The results of the study stated that return on assets (ROA) partially did not have a significant effect on profit quality; debt to equity ratio (DER) partially does not have a substantial effect on profit quality; the size of the company partially has a considerable effect on the quality of profits; and investment opportunity set (IOS) partially have a substantial influence on the quality of profits. Meanwhile, the overall impact was 58.2%, and 41.8% was influenced by other variables that were not studied.